2016
DOI: 10.4314/tjpr.v15i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coagulation factors and inflammatory cytokines on development of acute myocardial infarction in patients younger than 60 years

Abstract: Purpose: To investigate the effects of coagulation factors and inflammatory cytokines on acute myocardial infarction (AMI) development in patients younger

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…Our study also reported higher total treatment effectiveness and safety profiles in the experimental group vs. the control group. These results are consistent with those reported by other scholars [18].…”
Section: Discussionsupporting
confidence: 94%
“…Our study also reported higher total treatment effectiveness and safety profiles in the experimental group vs. the control group. These results are consistent with those reported by other scholars [18].…”
Section: Discussionsupporting
confidence: 94%
“…Полученные нами данные отличаются от данных ряда авторов, которые установили связь между полиморфными вариантами генов, включенных 17]. Также выявлено, что мутантный аллель А полиморфного варианта rs1977963 (FII), увеличивает риск развития ИМ у пациентов с ИБС [18].…”
Section: Introductionunclassified